STRUCTURAL CHARACTERISTICS OF UROCHLOA BRIZANTHA CV DUNAMIS DURING ITS ESTABLISHMENT SUBJECTED TO DIFFERENT DOSES OF NITROGEN - Saraiva, Raylene Marcelino; Barros, Josielto dos Santos; Martins, Athila Damasceno (Seven Editora, 2024)
Dunamis Grass is a hybrid cultivar formed by the junction of two other brachiarias, Marandu (Urochloa brizantha) and Decumbens (Decumbens cv. Basilisk), known for having rustic characteristics and resistance to biotic and abiotic factors. The objective of this study was to evaluate the agronomic characteristics of Dunamis grass under a greenhouse cutting regime with three doses of nitrogen fertilization (50, 100 and 150mg/dm³ of N) plus control (without fertilization) in a completely randomized design with six replications. Structural characteristics (average leaf length, number of tiller leaves, final leaf length, total number of leaves in senescence, number of dead leaves, maximum plant height, number of tiller per plant, number of tiller per pot) will be evaluated. The experiment will be conducted at the Centro Universitário Tocantinense Presidente Antônio Carlos – (UNITPAC), located in the north of Tocantins. DOI:https://doi.org/10.56238/sevened2024.032-010